Normalized circulating Tfh and Th17 associates with improvement in myasthenia gravis treated with ofatumumab - Song, Xiaodong; He, Yang; Huo, Yang; Jiang, Hong; Yu, Yao; Sun, Yue; Liu, Zunjing; Zhang, Zhaoxu (Frontiers in Immunology, 2024)
Objective To assess the effect of B cell depletion therapy (BCDT) on circulating T follicular helper (cTfh) and circulating T helper 17 (cTh17) cells and its relation to clinical improvement in patients with myasthenia gravis (MG). Methods 28 anti-AchR positive MG patients treated with ofatumumab and 28 healthy controls (HCs) were included. Frequencies of cTfh and cTh17 cells were monitored by flow cytometry at baseline and 4, and 12 weeks after the initial dose ofatumumab. Serum cytokines associated with cTfh and cTh17, including IL-6, IL-21, and IL-17, were also analyzed. Results The frequency of cTfh and cTh17 significantly increased in MG patients compared with HCs. Additionally, elevated levels of both T-cell subsets correlated with MG severity. During the follow-up, cTfh and cTh17 return to normal after BCDT. Furthermore, the decrease in cTfh and cTh17 was associated with MG scores improvement over time. Notably, cTfh- and cTh17-related cytokines, including IL-6, IL-21, and IL-17, exhibited a marked decrease following ofatumumab therapy. Conclusions Abnormal expansion of cTfh and cTh17 cells may be key features in the immunopathology of MG. Their levels returned to normal after BCDT, which was closely correlated with clinical amelioration. This result suggests that these two T-cell subsets may be targets for BCDT treatment of MG.